AM-PAC "6-Clicks" Functional Assessment Scores Predict Acute Care Hospital Discharge Destination. Issue 9 (1st September 2014) - Jette, Diane U.; Stilphen, Mary; Ranganathan, Vinoth K.; Passek, Sandra D.; Frost, Frederick S.; Jette, Alan M.
Abstract : Background: Physical therapists and occupational therapists practicing in acute care hospitals play a crucial role in discharge planning. A standardized assessment of patients' function could be useful for discharge recommendations. Objectives: The study objective was to determine the accuracy of "6-Clicks" basic mobility and daily activity measures for predicting discharge from an acute care hospital to a home or institutional setting. Design: The study was retrospective and observational. Methods: "6-Clicks" scores obtained at initial visits by physical therapists or occupational therapists and patients' discharge destinations were used to develop and validate receiver operating characteristic curves for predicting discharge destination. Positive predictive values (PPV), negative predictive values (NPV), and likelihood ratios were calculated. Results: Areas under the receiver operating characteristic curves for basic mobility scores were 0.857 (95% confidence interval [CI]=0.852, 0.862) and 0.855 (95% CI=0.850, 0.860) in development and validation samples, respectively. Areas under the curves for daily activity scores were 0.846 (95% CI=0.841, 0.851) and 0.845 (95% CI=0.840, 0.850) in development and validation samples, respectively. Cutoff scores providing the best accuracy for determining discharge destination were 42.9 for basic mobility and 39.4 for daily activity. For basic mobility, the PPV was 0.748 and the NPV was 0.801 in both development and validation samples. For daily activity, the PPVs were 0.787 and 0.784 and the NPVs were 0.748 and 0.746 in development and validation samples, respectively. Limitations: Limitations included lack of information on the rater reliability of "6-Clicks" instruments, use of surrogate data for some discharge designations, and use of a clinical database for research purposes. Conclusions: This study provides evidence of the accuracy of "6-Clicks" scores for predicting destination after discharge from an acute care hospital.